Pharmacologic vitreolysis [Farmakolojik vitreolizis] - (:unkn) unknown (Gazi Eye Foundation, 2015)
Pharmacologic vitreolysis is an alternative treatment to surgery, aiming to cause vitreous liquefaction and complete posterior vitreous separation from the retina effectively and safely. Several agents and enzymes have been explored for this purpose. Of these, plasmin and ocriplasmin have shown the most promise for clinical application. The recent approval by the US Food and Drug Administration of ocriplasmin for the treatment of symptomatic vitreomacular adhesion has brought new attention to the field of pharmacologic vitreolysis. This article summarizes enzymatic vitreolysis and current knowledge and status of investigations regarding ocriplasmin-induced pharmacologic vitreolysis, and offers some evidence-based considerations for its use. © 2015 Gazi Eye Foundation. All Rights Reserved.
Keywords: Ocriplasmin; Pharmacologic vitreolysis; Vitreomacular adhesion; Vitreous